Special Soviet Cars for Disabled People and their Operation in Kharkiv Region (late 1940's – 1990-ies) - Устименко, Олександр (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article deals with the history of development of Soviet fundamentally new special microcars for disabled people. All modifications for disabled by ZAZ vehicles are briefly considered. The conditions in which microcars and vehicles with manual control were issued, their repair and operation in Kharkiv region are also being investigated. The final conclusion is that Soviet microcars and vehicles with manual control were peculiar phenomenon because disabled people had got them for using not like passengers (as it was in Europe and the USA), but like drivers. It is also proved that increasing of the number of such special vehicles led to proportional increasing of disabled people who claimed them.